2019
DOI: 10.1002/lary.27764
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of olfaction after sinus surgery for chronic rhinosinusitis: A review

Abstract: Objective Investigation of the postoperative olfactory function after sinus surgery for chronic rhinosinusitis (CRS) with and without polyps in a review. Data Sources PubMed. Review Methods A comprehensive literature search was conducted through June 2018 using relevant keywords. The titles/abstracts were reviewed to identify studies evaluating the sense of smell in CRS‐patients pre‐ and postoperatively by either using the whole or parts of the University of Pennsylvania Smell Identification Test or the Sniffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 56 publications
(256 reference statements)
1
31
0
Order By: Relevance
“…Other therapies such as antileukotrienes, corticosteroid sinus implants, or aspirin desensitization have also been shown to improve smell loss in patients with CRS. Because recent studies have demonstrated a poor middle-to long-term efficacy of endoscopic sinus surgery in smell loss, the role of CRS surgery in improving the sense of smell, apart from the effect of first surgeries, 8 remains under debate and should not be used as the unique indication criteria for CRS surgery.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Other therapies such as antileukotrienes, corticosteroid sinus implants, or aspirin desensitization have also been shown to improve smell loss in patients with CRS. Because recent studies have demonstrated a poor middle-to long-term efficacy of endoscopic sinus surgery in smell loss, the role of CRS surgery in improving the sense of smell, apart from the effect of first surgeries, 8 remains under debate and should not be used as the unique indication criteria for CRS surgery.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Various studies, including systematic reviews, have shown improvements in olfaction following FESS, as in the current study. 3,12,26,27 The added gains in chronic rhinosinusitis with nasal polyps patients may again be due to the removal of the obstructive pathology. However, reports have also shown a lack of olfactory improvement after FESS, 28 with no predictive correlation to the severity of chronic rhinosinusitis, presence of nasal polyps or allergy status.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory dysfunction is a "cardinal" symptom in CRS and affects the majority of patients with this disease. 7,8 Furthermore, patients identify OD as one of the top three most important symptoms in which they would like to see post-treatment improvement. 17 Prior work suggests that some amount of the OD seen in patient with CRS may be related to non-CRS factors such as age and medical comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…18 While ESS improves olfaction for certain patients, the results can be unpredictable and difficult to counsel patients surrounding post-operative expectation. 8 One primary limitation evident within the available literature on this subject is the lack of comparisons of OD in healthy, control populations. As such, previous findings of olfactory outcomes after ESS may be confounded by the fact that OD is multi-factorial and that some patients with CRS suffer from levels of OD similar to normative data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation